Art Nouveau : van Old England tot het Palais Stoclet - Bral, Guido Jan, 1953-; Strauven, Francis, 1942- (Tielt : Lannoo, 2008)
Elsene, Sint-Gillis, Brussel, Ukkel, Gent, Antwerpen, Berchem, Etterbeek, Schaarbeek, O -l -Vr-Waver, Sint-Joost-ten-Node, Luik, Bergen, Voormezele
Keywords: Art nouveau